Singapore in a Post-Kyoto World : Energy, Environment and the Economy. - Doshi, Tilak (Institute of Southeast Asian Studies, 2015)
Singapore had, by the 1980s, emerged as one of the world's great oil refining and trading centres, with the "East of Suez" region within its sphere of influence. The city-state's policy-making went against the grain in much of its practice of economic development. It ensured that energy products were bought and sold in the domestic market at essentially global prices, in contrast to the common practice in developing countries of subsidizing energy fuels for social equity. Without a drop of oil of its own, Singapore also managed to attract large foreign investments in the capital-intensive oil.